The Information System For The Mosque In Tebat Agung Village Is Website-based - Apriansyah, Apriansyah; Putri, Yelda Pertia Merlinda (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2024)
The mosque is a place of worship for Muslims to Allah SWT as the main means of carrying out prayers, recitations, lectures and other Islamic religious activities. At the mosque in Tebat Agung village several problems were encountered, namely the mosque system was still manual, where the process of recording Friday prayer officers, member lists, obligatory prayer schedules were still written using markers on whiteboards, cash financial management was still calculated using calculators and recorded using books and announced once a week, as well as activities held only announced using loudspeakers. This is vulnerable to uneven distribution of information, data loss, data errors. Based on the problems above, the author took the initiative to design a mosque information system website that can help manage cash finances quickly and easily and disseminate information effectively and transparently. Data collection uses observation, interviews and literature study methods, while system development uses the waterfall method. This system is useful for helping mosque administrators, especially treasurers and secretaries, in managing mosque cash, Friday prayer schedules, prayer schedules, management structures, activity agendas, making it easier to prepare monthly reports and making it easier to distribute information evenly, increasing the sense of trust in the relevant mosque administrators. mosque finances and also increasing community aspirations in religious activities. The testing stage aims to ensure the input and output are in accordance with the user's wishes. A total of 13 cases had satisfactory results with a system validity calculation of 85%.